Does rural landowner identity shape the adoption of sustainable farming practices?. Issue 3 (2nd July 2020) - Groth-Joynt, Theresa M.; Curtis, Allan; Mendham, Emily; Toman, Eric
ABSTRACT: The increasing proportion of rural landowners who do not identify as farmers has meaningful consequences for efforts to influence the adoption of sustainable farming practices. This article aims to contribute to the knowledge base for those responding to that challenge. A survey of 2000 rural landowners in south eastern (SE) Australia employed a 12-item collective occupational identity construct to explore the extent farmer occupational identity explained variance in landowner implementation of three recommended sustainable farming practices. Practices included the planting of perennial pasture and lucerne, testing soils for nutrient status, and the application of lime to address soil acidity. Logistic regression indicated farmer occupational identity enhanced the explanatory power of models exploring implementation of those practices. Four distinct rural landowner cohorts were identified based on farmer identity: full-time, part-time, hobby and non-farmers. Part-time and full-time farmers are similar in that they are focused on farming as a business. By comparison, hobby and non-farmers give a higher priority to biodiversity and amenity values associated with their properties. The classification and knowledge of the attributes of each cohort can be used to support more effective engagement with the increasingly diverse population of rural landholders in many of the regions in SE Australia.